2021
DOI: 10.2147/pgpm.s304747
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR Detection of mtDNA/gDNA Ratio in Embryo Culture Medium for Prediction of Embryo Development Potential

Abstract: Purpose The ratio of mitochondrial DNA to genomic DNA (mtDNA/gDNA) in embryo culture medium as a predictor of embryonic development is a new method of noninvasive embryo screening. However, current tests based on this concept have proven inconsistent. The aim of this study was to define the predictive value of the ratio of mtDNA/gDNA for embryonic developmental potential. Materials and Methods We used digital PCR to measure mtDNA/gDNA ratios in day 3 culture media of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Studies have shown that the quality of transferred embryos is one of the key factors affecting the pregnancy outcome of patients. [16] The morphological rating of an embryo reflects a very short timepoint in its development and cannot represent its entire development, but it reflects its developmental potential to some extent. [17] Clinical pregnancy and IRs improve with the embryo grade, therefore, the higher the embryo quality, the better the clinical pregnancy results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the quality of transferred embryos is one of the key factors affecting the pregnancy outcome of patients. [16] The morphological rating of an embryo reflects a very short timepoint in its development and cannot represent its entire development, but it reflects its developmental potential to some extent. [17] Clinical pregnancy and IRs improve with the embryo grade, therefore, the higher the embryo quality, the better the clinical pregnancy results.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have been performed to evaluate mtDNA as a potential biomarker of embryo vitality. However, there is a lot of controversy as studies performed have reached contradicting conclusions [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, advanced and sensitive molecular genetic approaches have been successfully applied to spent embryo culture media (SECM), which can be easily obtained during in vitro embryo culture. It is possible to analyze small amounts of cell-free DNA (cfDNA), mitochondrial DNA, microRNA, and long non-coding RNA secreted from embryos using real-time polymerase chain reaction (PCR) or digital PCR, as well as next-generation sequencing (NGS) [5][6][7]. In addition, studies have evaluated the developmental ability of embryos by analyzing substrates and metabolites produced during in vitro culture, which will be discussed further below [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%